KINERJA PRODUKSI DAN NILAI TAMBAH AGROINDUSTRI JAMU BUBUK DI DESA ASTO MULYO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Measi Arsita; Muhammad Irfan Affandi; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purpose of the study is to analyze the production performance and added value of powdered herbal agroindustry. This research was carried out in Asto Mulyo Village, Punggur Subdistrict, Lampung Tengah District, which involved agroindustrial owners, industrial agencies, supermarket managers, self-service consumers, and community leaders. Data are analyzed quantitatively and statistically. The results of the research, herbal powder production performance is already good, with productivity of 5,16 kg/HOK, meaning that every one HOK of labor is able to produce as much as 5.16 kg powdered herbs, although the capacity value of powdeed herbal products is already high (91,00 percent). The R/C of agroindustry is 1.88, meaning that the agroindustry is good and profitable. The added value of each variant of different herbs, namely curcuma is amounting to Rp24,854.42 per kg of raw material; turmeric is amounting to Rp25,351.27 per kg of raw material, kencur of Rp12,352.29 per kg of raw material, and ginger in the amount of Rp21,853.94 per kg of raw material.Key words: added value, herbal powder, production performance